Advanced Diagnostic Imaging of the Lumbar Spine for Radiological Assessment-An Updated Review - Abulkhair, Sattam Mansour; Marzog Awwad Alotaibi; Ahmad Ali Almahmadi; Ghanem Ghazi Menwer Alshammari; Abdullah Ahmed Ali Faqihi; Anwar Rifadah Abdullah Alanazi; Anas Mohammed Mohammed Hakami; Hussam Ahmed Hassan Rayyani; Ali Ahmed Samhan Alsuhaymi; Abdulaziz Abdullah Masad Almutiri; Hassan Salman A Almutairi; Omar Mohammed Muflih Alrashdi; et al. (Saudi Journal of Medicine and Public Health, 2025)
Background: Low back pain is a major global health problem and one of the most frequent causes of medical consultation and imaging referral. Its etiology ranges from benign degenerative changes to serious conditions such as infection, trauma, malignancy, and postoperative complications. Selecting the appropriate imaging modality is essential for accurate diagnosis, optimized patient management, and avoidance of unnecessary radiation exposure. Aim: This review aims to provide an updated, comprehensive overview of imaging modalities used in the diagnostic assessment of the lumbar spine, highlighting indications, strengths, limitations, and clinical applications in common and complex lumbar spine pathologies. Methods: A narrative review approach was used to synthesize current evidence and established guidelines, particularly the American College of Radiology (ACR) appropriateness criteria. Imaging modalities discussed include plain radiography, computed tomography (CT), magnetic resonance imaging (MRI), ultrasonography, nuclear medicine techniques, and angiography, with correlation to anatomical, degenerative, infectious, neoplastic, traumatic, and postoperative conditions. Results: Plain radiographs remain a first-line tool for assessing gross structural abnormalities, while CT provides superior evaluation of osseous detail and traumatic injuries. MRI offers unparalleled soft tissue contrast and is the modality of choice for disc disease, spinal canal masses, infection, malignancy, and postoperative complications. Nuclear medicine and angiographic studies serve complementary roles in functional assessment and vascular pathology, respectively. Conclusion: An evidence-based, patient-centered imaging approach tailored to clinical presentation and suspected pathology is critical in lumbar spine evaluation. Integration of multimodal imaging enhances diagnostic accuracy and improves clinical outcomes.